Laparoscopic Lavage in the Management of Hinchey III/IV Diverticulitis - Kiely, Maria X.; Yao, Mengdi; Chen, Lilian (Clinics in Colon and Rectal Surgery, 2021)
Diverticulitis manifestations may cover a spectrum of mild local inflammation to diffuse feculent peritonitis. Up to 35% of patients presenting with diverticulitis will have purulent (Hinchey grade III) or feculent (Hinchey grade IV) contamination of the abdomen, with a high-associated morbidity and mortality. Surgical management may involve segmental resection with or without restoration of bowel continuity. However, emergency resection for diverticulitis can be associated with high mortality rates, as well as low stoma reversal rates at 1 year. Therefore, laparoscopic peritoneal lavage has been proposed for use in selected patients with purulent peritonitis. The topic of laparoscopic peritoneal lavage for the treatment of perforated diverticulitis in the literature has been controversial. Our review of the recent data show that laparoscopic lavage may be safe and feasible in select patients with similar rates of mortality and major morbidity. There is, however, a concern regarding an associated higher rate of postoperative abscess and early reintervention risk.
Keywords: diverticulitis; laparoscopic peritoneal lavage; perforated diverticulitis; purulent peritonitis